EMBODIED EXPERIENCES OF DRAWING: A PHENOMENOLOGICAL INQUIRY INTO STRESS AND EVERYDAY LIFE IN ART EDUCATION - Ankyiah, Francis (ARTISTIC : International Journal of Creation and Innovation, 2023)
Drawing's impact on students' stress levels and coping with daily life is underexplored. This study used a phenomenological approach to understand how undergraduates experience drawing in art studio courses. Five art students were interviewed during regular assignments, and Moustakas' method was used to analyse the data. Three themes emerged: drawing as an "escape" from worries, a mindfulness practice fostering relaxation and present moment awareness, and beneficial for stress management and coping skills applicable to other areas of life. Immersion in drawing cultivates mind-body awareness, aiding students in managing stress. It buffers academic demands and enhances overall well-being, but can also induce stress during heavy workloads. This study offers qualitative insights into drawing as stress relief and emotional regulation for art students navigating educational and everyday demands.